Antecedents and Consequences of Tax Avoidance on Company Value - Kiryanto Kiryanto; Nindika Ayulinar Putri Susanti (Jurnal Akuntansi Indonesia)
ABSTRACT The research aims to determine the influence of corporate social responsibility and audit quality variables on company value which is mediated by tax avoidance. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2018-2021. Sampling used a purposive sampling method anda obtained 66 company samples. The analysis technique used in SmartPLS 3.29 programs. The research results show that CSR disclosure has no effect on taxeavoidance, but auditequality has negative and significant effect on taxeavoidance. Apart from that, CSRsdisclosure has no effect on company value, while audit qualityyhas a positive and significanteeffect on company value. Even though the research result show that tax avoidance has an effect on company value, tax avoidance is not able to mediate the relationship between CSR disclosure and audit quality on company value. The contribution of this research is to add to the literature review regarding Tax Avoidance research Keyword : Tax Avoidance, Firm Value, Audit Quality, Corporate Social Responsibility